Role of Mobile-Assisted Language Learning in Improving Vocabulary Mastery among EFL Students - Caroline V. Katemba (Yayasan Insan Cipta Medan, 2025)
This study investigated the role of Mobile-Assisted Language Learning (MALL) in improving vocabulary mastery among English as a Foreign Language (EFL) students at MAN Labuhanbatu. A qualitative descriptive design was employed to explore how mobile applications support vocabulary learning in this context. Data were collected through classroom observations, semi-structured interviews with two English teachers and twenty-four Grade XI students, and document analysis of lesson plans and student task results. Vocabulary mastery was measured through pre-test and post-test scores over a six-week period of MALL integration using applications such as Quizlet and Duolingo. The findings indicated that MALL enhanced students’ vocabulary acquisition by providing greater exposure to target words, interactive learning activities, and personalized practice opportunities. The average vocabulary score increased from 65.42 in the pre-test to 80.58 in the post-test, with notable improvements in word meaning recognition, spelling accuracy, and contextual usage in writing. Students reported higher motivation and engagement, while teachers noted more active participation during lessons. However, challenges such as limited internet access, inconsistent task completion, and passive engagement with applications were also identified. It can be concluded that MALL serves as an effective supplementary tool for vocabulary instruction in the madrasah context, provided it is integrated into structured learning activities and supported by consistent teacher guidance. The study recommends further research on the long-term effects of MALL and its application in other areas of language learning.